Email communication in a developing country: different family physician and patient perspectives. Issue 1 (1st January 2016) - Makarem, Nisrine N.; Antoun, Jumana
Abstract : Background: Email communication between physicians and patients could improve access to and delivery of health care. Most of the literature studies about email communication between physicians and patients have been conducted in developing countries. Therefore, this study aims to analyze the practices, attitudes, and barriers of both physicians' and patients' use of email within the same health care setting of a developing country. Methods: A cross-sectional paper-based survey was conducted among 39 physicians and 500 patients at the Family Medicine clinics of the American University of Beirut, a tertiary academic medical center. Results: Most of the surveyed patients and physicians reported that they would like to communicate through email and agreed that it is useful. However, only 19% of the patients have ever communicated with their physicians via email, and only 5.1% of physicians have often communicated with their patients via email. Almost half of the patients surveyed were unaware of the possibility of this form of communication, and only 17% reported that their physician offered them his or her email address. In addition, physicians and patients did not agree on the services to be provided by email communication. For instance, almost half of the patients indicated consultation for an urgent medical matter as suitable for email communication. Conclusion: The use of email communication in health care is still scarce. Patients and physicians have different perspectives of its use and importance. Further rigorous research is needed to clarify the advantages and disadvantages of this form of communication, especially in the developing world. Interested physicians are encouraged to establish appropriate personal policies for email communication with adequate announcement and patient education plans.